Artificial emotion modeling based on container (CUP) algorithm - Gao, Yuan; Li, Qing (Journal of intelligent & fuzzy systems, 2020)
Human emotion is an extremely complex social phenomenon that dominates many social phenomena. The paper proposes a method of emotional modeling in the context of complex systems based on the container model, which is more intuitive and can be solved than the conventional emotional modeling methods. Meanwhile the container algorithm also has the advantages of high parallelism, so it has practical significance for the simulation and analysis of emotions.